Burnout in humanitarian work: A qualitative study on the life experiences of workers in Malaysia - Cheong, Sue Jen; Ng, Chong Guan; Shoesmith, Wendy Diana; Yau Koh, Eugene Boon; Ping Pang, Nicholas Tze; Wider, Walton; Udang, Lester Naces (EnPress Publisher, 2024)
Humanitarian workers face numerous challenges when providing assistance to people affected by natural disasters, armed conflicts, and other crises, which often leads to burnout and psychological distress. This qualitative study investigates the interplay of factors that contribute to burnout among Malaysian employees of a refugee-focused humanitarian organization. Ten staff members participated in focus group discussions, which revealed five themes: positive and meaningful emotions; difficult and negative emotions; vicarious trauma, stress, and burnout; work environment, culture, and managerial policies; and structural and governmental stressors. The study emphasizes the need for improved support and resources for humanitarian workers, as well as enhanced organizational policies and practices to prevent and mitigate burnout. The findings suggest that culturally adapted interventions, such as Acceptance and Commitment Therapy (ACT), can help humanitarian workers address their unique psychological challenges. More research is needed to examine the issues present within humanitarian organizations using qualitative methods and adapt appropriate interventions to prevent the development of psychopathology in these settings.